The Effectiveness of Using the Media Game Jumping Word Circles in Teaching Arabic Vocabulary - Yoke Suryadarma; Agung Nurcholis; Anggita Hilaul Pikri (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2023)
The determinant purpose of this research was to determine the effectiveness of the media game word circle jumping in teaching Arabic vocabulary in the student class six of Madrasah Ibtidaiyah Nurul Ulum Pegiringan for the academic year 2022/2023. The research based on the type of true experimental research. The population used were 60 students from class Six at Madrasah Ibtidaiyah Nurul Ulum Pegiringan, but it was done by random sampling, taken only 36 students and divided into two groups, namely experiments group and controls group which each contains 18 students. The data collection techniques used were 1) Tests, 2) Observations, 3) Interviews and 4) Documentation. The data analysis used was descriptive analysis, normality test, homogeneity test and Independent-Sample T-Test. The finding result showed that the Sig.2-tailed value is 0.080, which means that the Sig.2-tailed value is 0.080>0.05, then Ho is accepted and Ha is rejected, so the posttest values between experiment and controls group arenot significantly different. And it can be inferred that there was no effectiveness of the application of the word circle jumping game media in teaching Arabic vocabulary in class 6 in academic year 2022/2023. After accomplishing this research, it is really hope that this research could be used as one of the references in using game media in teaching Arabic vocabulary for the next other researchers, espesially in how to conduct this application of the word circle jumping game media in learning Arabic vocabulary properly.